Law of succession - Musyoka, William (LawAfrica, 2006)
This text broadly and comprehensively covers the area of law of succession in Kenya. It exposes the substantive succession legal regime applying in Kenya as well as the Kenyan probate practice. It is tailored specifically for the legal practitioner, the magistrate and judge and the law student. Some of the key areas covered include; Testate Succession; Intestacy; Post-Mortem alterations among many others. It is currently the only text on succession law in Kenya.